Failure to follow medication changes made at hospital discharge is associated with adverse events in 30 days. (20th May 2020) - Weir, Daniala L.; Motulsky, Aude; Abrahamowicz, Michal; Lee, Todd C.; Morgan, Steven; Buckeridge, David L.; Tamblyn, Robyn
Abstract: Objective: To evaluate the hypothesis that nonadherence to medication changes made at hospital discharge is associated with an increased risk of adverse events in the 30 days postdischarge. Study Setting: Patients admitted to hospitals in Montreal, Quebec, between 2014 and 2016. Study Design: Prospective cohort study. Data Collection: Nonadherence to medication changes was measured by comparing medications dispensed in the community with those prescribed at hospital discharge. Patient, health system, and drug regimen‐level covariates were measured using medical services and pharmacy claims data as well as data abstracted from the patient's hospital chart. Multivariable Cox models were used to determine the association between nonadherence to medication changes and the risk of adverse events. Principal Findings: Among 2655 patients who met our inclusion criteria, mean age was 69.5 years (SD 14.7) and 1581 (60%) were males. Almost half of patients (n = 1161, 44%) were nonadherent to at least one medication change, and 860 (32%) were readmitted to hospital, visited the emergency department, or died in the 30 days postdischarge. Patients who were not adherent to any of their medication changes had a 35% higher risk of adverse events compared to those who were adherent to all medication changes (1.41 vs 1.27 events/100 person‐days, adjusted hazard ratio: 1.35, 95% CI: 1.06‐1.71). Conclusions: Almost half of all patients were not adherent to some or all changes made to their medications at hospital discharge. Nonadherence to all changes was associated with an increased risk of adverse events. Interventions addressing barriers to adherence should be considered moving forward.